Impacto del proyecto naf en los conocimientos contables y tributarios adquiridos por los estudiantes de la Utmach 2023-2024. - Medina Macias, Julio Andres (Machala : Universidad Técnica de Machala, 2024)
This research work aims to evaluate the impact of the Accounting and Tax Support Center (NAF) project on the accounting and tax knowledge acquired by students of the Technical University of Machala (UTMACH) during the period 2023-2024. The research seeks to identify challenges and difficulties of students in their participation in the NAF project and also to describe the services offered to the community according to the information obtained through an interview directed to the project manager and the participation of students in the project through a survey. The methodology of the study maintains a qualitative approach with a constructivist paradigm and an inductive method. The research design is analytical and non-experimental, using techniques such as the interview form and survey guide. The findings indicate that the implementation and structure of the NAF project significantly improve the practical application of accounting and tax knowledge among participating students. Through their participation they not only improve their technical skills but also develop professional competencies such as financial and tax management. The NAF project fosters a positive contribution to the community by providing free accounting assistance to low-income individuals. The project serves as a vital experiential learning platform that bridges theoretical knowledge and practical application, benefiting students and the community. This research underscores the importance of such initiatives in higher education to foster comprehensive skills development and community engagement.
Este trabajo de investigación pretende evaluar el impacto del proyecto Núcleo de Apoyo Contable y Fiscal (NAF) en los conocimientos contables y tributarios adquiridos por los estudiantes de la Universidad Técnica de Machala (UTMACH) durante el periodo 2023-2024. La investigación busca identificar desafíos y dificultades de los estudiantes en su participación en el proyecto NAF y también describir los servicios ofrecidos a la comunidad según la información obtenida a través de una entrevista dirigida al encargado del proyecto y la participación de los estudiantes en el proyecto mediante una encuesta. La metodología del estudio conserva un enfoque cualitativo con un paradigma constructivista y un método inductivo. El diseño de la investigación es analítico y no experimental, utilizando técnicas como la ficha de entrevista de entrevista y guía de encuesta. Los hallazgos indican que la implementación y estructura del proyecto NAF mejoran significativamente la aplicación práctica de los conocimientos contables y fiscales entre los estudiantes participantes. A través de su participación no solo mejoran sus habilidades técnicas sino también desarrollan competencias profesionales como la gestión financiera y tributaria. El proyecto NAF fomenta una contribución positiva a la comunidad al brindar asistencia contable gratuita a personas de bajos ingresos. El proyecto sirve como una plataforma vital de aprendizaje experimental que une el conocimiento teórico y la aplicación práctica, beneficiando a estudiantes y a la comunidad. Esta investigación subraya la importancia de este tipo de iniciativas en la educación superior para fomentar el desarrollo integral de habilidades y la participación comunitaria.
Keywords: PROYECTO NAF; CONTABILIDAD; TRIBUTACION; FISCALIDAD